Acute high-intensity interval exercise versus moderate-intensity continuous exercise in heated water-based on hemodynamic, cardiac autonomic, and vascular responses in older individuals with hypertension - Marçal, Isabela Roque [UNESP]; Amaral, Vanessa Teixeira do [UNESP]; Fernandes, Bianca [UNESP]; Abreu, Raphael Martins de; Alvarez, Cristian; Guimarães, Guilherme Veiga; Cornelissen, Véronique A; Ciolac, Emmanuel Gomes [UNESP] (Taylor & Francis, 2022)
Objectives: This crossover study design aimed to assess hemodynamic, cardiac autonomic, and vascular responses to high-intensity interval (HIIE) vs moderate-intensity continuous exercise (MICE) in older individuals with hypertension. Methods: Twenty (67 ± 7 y) older individuals with hypertension were randomly assigned to perform HIIE, MICE, or control (CON) sessions in the heated swimming pool (30–32°C). Blood pressure (BP), arterial stiffness, endothelial reactivity, and heart rate variability (HRV) were measured pre, post, and 45 min (recovery) after each intervention followed by 24-h ambulatory BP and HRV. Results: One single aerobic exercise session was not effective to provoke post-exercise hypotension and vascular improvements. HIIE was superior to MICE and CON to increasing parasympathetic modulation at post and recovery. Exercise sessions showed to disturb the autonomic system at nighttime compared to CON. Conclusions: These results may have important implications in water-based therapy and the elderly with hypertension.
Keywords: Aerobic exercise; blood pressure; heart rate variability; older adults; post-exercise hypotension